The Citizen and the making City - Fisher, Roy 1930-2017 (Bloodaxe Books, 2022)
An early prose work relating to Roy Fisher and his native city of Birmingham - previously thought to have been lost - which was the precursor of 'City', his signature collage of poetry and prose including prose sections from 'The Citizen'
Keywords: Fisher, Roy -- 1930-2017; Fisher, Roy / 1930-2017 / City; Birmingham (England) / Literary collections; England / Birmingham; Literary collections